Alienation and its Avatars: Clarifying Measurement Issues (Journal of Organizational Psychology, 2018)
Integrating psychology-, social psychology-, sociology- and management-based perspectives, weinvestigate eight alienation-related constructs and dimensions using factor analyses to determine their dimensionality. Results based on factor analyses demonstrate that the dimensions proposed by Seeman (1959) for alienation – meaninglessness, powerlessness, self-estrangement, social isolation, and normlessness – do not converge toward three general measures of alienation (student alienation, work alienation, and Marxist alienation).
Keywords: Psychology; Business Management; social psychology